Stability-indicating HPLC Method Development and Validation for Quantitative Analysis of Leniolisib: A Novel Selective PI3K\(δ\) Inhibitor - Panchumarthy Ravi Sankar; Kamma Harsha Sri; Ch. V. Prasada Rao; Kancharla Pujitha (Pharmaceutical Research: Recent Advances and Trends Vol. 10, 2024)
A novel, robust RP-HPLC method has been developed and validated for the precise quantification of Leniolisib, a newly approved treatment for activated phosphoinositide-3 kinase delta syndrome (PI3K\(δ\)). This method is simple, reliable, sensitive, and reproducible, enabling the determination of Leniolisib using a single chromatographic system without modifications in detection wavelength or mobile phase composition. Separation was carried out on a Waters X-Terra RP-18 column (4.6 x 150 mm, 3.5 µm) with a mobile phase of acetonitrile and 0.1% TEA (pH-2.5, OPA) in a 40:60 ratio, at a flow rate of 1 ml/min. Detection was performed at 222.3 nm using a UV detector, with a total run time of six minutes and an elution time of 3.978 minutes. The method demonstrated excellent linearity (r² = 0.9996), with a relative standard deviation (RSD) below 2% and an average recovery greater than 100%. Validation included assessments of linearity, precision, specificity, accuracy, and robustness, confirming its suitability for the quality control of Leniolisib in bulk and tablet dosage forms. Stability studies were conducted via forced degradation experiments. The percentage of degradation observed under acid, alkali, peroxide, reduction, thermal, photolytic, and hydrolysis conditions was 12.0 %, 13.6 %, 15.7 %, 2.1 %, 1.3%, 10.1 %, and 1.0%, respectively. This validated RP-HPLC method is therefore suitable for the routine quantification of Leniolisib in pharmaceutical operations and analytical laboratories.